HUBUNGAN STATUS GIZI DENGAN KEJADIAN TB PARU DI RUMAH SAKIT KHUSUS PARU SUMATERA UTARA TAHUN 2023 - Rupang, Ernita Rante; Ginting, Amnita Anda Yanti; Veronika, Sovia (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Nutritional status is a value that shows the balance between the absorption of nutrients from food and the nutritional needs required by a person's body. Pulmonary TB is a disease caused by Mycobacterium tuberculosis and can be transmitted through air or droplets. Pulmonary TB sufferers who have less than normal nutritional status require a longer healing time and it is possible that pulmonary TB disease can recur. This study aims to determine the relationship between nutritional status and the incidence of pulmonary TB at the North Sumatra Special Lung Hospital in 2023. This research was conducted on April 5 - 18 2023. This research method uses a cross sectional design using a purposive sampling technique with a total of 88 respondents. This research instrument uses observation sheets, scales, and measuring tape. In this research, the data analysis used is univariate and bivariate analysis. The research results showed that of the 88 respondents there were 49 respondents (55.7%) with a mild level of underweight nutritional status, and 59 (67.0%) respondents had positive (+) acid-fast bacteria results. The statistical test results show that there is a relationship between nutritional status and the incidence of pulmonary TB at the North Sumatra Special Lung Hospital in 2023 with the results of the chi-square test, obtained p value = 0.002. Therefore, the nutritional status of pulmonary TB patients needs to be improved and paid attention to in order to speed up the healing process for pulmonary TB patients with health education provided by health services.